Lithiophilic-lithiophobic gradient interfacial layer for a highly stable lithium metal anode - Zhang, Huimin; Liao, Xiaobin; Guan, Yuepeng; Xiang, Yu; Li, Meng; Zhang, Wenfeng; Zhu, Xiayu; Ming, Hai; Lu, Lin; Qiu, Jingyi; Huang, Yaqin; Cao, Gaoping; et al. (Nature communications, 2018)
The long-standing issue of lithium dendrite growth during repeated deposition or dissolution processes hinders the practical use of lithium-metal anodes for high-energy density batteries. Here, we demonstrate a promising lithiophilic–lithiophobic gradient interfacial layer strategy in which the bottom lithiophilic zinc oxide/carbon nanotube sublayer tightly anchors the whole layer onto the lithium foil, facilitating the formation of a stable solid electrolyte interphase, and prevents the formation of an intermediate mossy lithium corrosion layer. Together with the top lithiophobic carbon nanotube sublayer, this gradient interfacial layer can effectively suppress dendrite growth and ensure ultralong-term stable lithium stripping/plating. This strategy is further demonstrated to provide substantially improved cycle performance in copper current collector, 10 cm 2 pouch cell and lithium–sulfur batteries, which, coupled with a simple fabrication process and wide applicability in various materials for lithium-metal protection, makes the lithiophilic–lithiophobic gradient interfacial layer a favored strategy for next-generation lithium-metal batteries. Lithium metal batteries suffer from the dendrite growth upon electrochemical cycling. Here the authors introduce a lithiophilic-lithiophobic gradient interfacial ZnO/CNT layer, which facilitates the formation of a stable solid electrolyte interphase, and suppresses the growth of lithium dendrite.